ANALYSIS OF POTENTIAL SUSTAINABILITY DURING THE COVID 19 PANDEMIC PERIOD USING THE MODEL SPRINGATE ON THE INDUSTRY CONSUMER GOODS ARE LISTING ON THE STOCK EXCHANGE INDONESIA IN 2020 - Yunita, Rini; Aziza, Nurna; Abdullah, Abdullah (JURNAL FAIRNESS, 2021)
This study aims to determine the potential bankruptcy of consumer goods industrial companies using the springate model. The population in this study are all consumer goods industry companies listed on the Indonesia Stock Exchange for the period 2020. This study uses a qualitative approach. The sampling technique used in this study was purposive sampling.Based on the sampling using purposive sampling, then obtained as many as 51 companies with 153 observations. The results show that the consumer goods industry manufacturing companies during the COVID-19 pandemic in 2020 have the potential to experience bankruptcy reaching 49.67%.